2019
DOI: 10.1038/s41598-019-53297-w
|View full text |Cite
|
Sign up to set email alerts
|

PD-1+ melanocortin receptor dependent-Treg cells prevent autoimmune disease

Abstract: Experimental autoimmune uveoretinitis (EAU) is a mouse model of human autoimmune uveitis marked by ocular autoantigen-specific regulatory immunity in the spleen. The melanocortin 5 receptor (MC5r) and adenosine 2 A receptor (A2Ar) are required for induction of post-EAU regulatory T cells (Tregs) which provide resistance to EAU. We show that blocking the PD-1/PD-L1 pathway prevented suppression of EAU by post-EAU Tregs. A2Ar induction of PD-1+FoxP3+ Tregs in uveitis patients was similar compared to healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…It is worth mentioning that a spontaneous recovery from EAU was observed in mice 75-90 days post-immunization with no further relapse. The main drivers of recovery are APC expressing high levels of A 2A ARs and the melanocortin 5 receptor, whose activation leads to increased CD73 and CD39 expression, with an increase of extracellular Ado concentrations which in turn promotes T reg activation and resolution of uveitis [82]. Based on these conflicting results, caution should be used when planning an A 2A ARs-based therapy for uveitis since whether an agonist or an antagonist will provide the better outcome might depend upon the stage of the disease.…”
Section: The Immunomodulatory Role Of a 2a Ars: Can Its Derailment Plmentioning
confidence: 99%
“…It is worth mentioning that a spontaneous recovery from EAU was observed in mice 75-90 days post-immunization with no further relapse. The main drivers of recovery are APC expressing high levels of A 2A ARs and the melanocortin 5 receptor, whose activation leads to increased CD73 and CD39 expression, with an increase of extracellular Ado concentrations which in turn promotes T reg activation and resolution of uveitis [82]. Based on these conflicting results, caution should be used when planning an A 2A ARs-based therapy for uveitis since whether an agonist or an antagonist will provide the better outcome might depend upon the stage of the disease.…”
Section: The Immunomodulatory Role Of a 2a Ars: Can Its Derailment Plmentioning
confidence: 99%
“…A mechanism of ocular immune privilege is the induction of systemic immunity against ocular antigen. We and others have found this regulatory immunity to emerge at resolution of uveitis (10,26,27,33). However, we have found that resolution of uveitis can occur without induction of post-EAU regulatory immunity (12,14).…”
Section: Discussionmentioning
confidence: 80%
“…The aim of this study is to further understand the role of the melanocortin-adenosinergic pathway in the induction of autoimmune uveitis. We have previously reported that the melanocortin-adenosinergic pathway is necessary for the induction of post-EAU regulatory immunity that provides resistance to relapse ( 11 , 14 , 26 , 27 ). Our previous work specifically showed that expression of the melanocortin 5 receptor (MC5r) on the post-EAU antigen presenting cell (APC) is required for activation of post-EAU regulatory T cells that express the adenosine 2A receptor (A2Ar).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that PD-1 + CD25 + CD4 + Treg cells require programmed cell death 1 (PD-1) stimulation through a melanocortin-adenosine pathway to suppress EAU. These Treg cells did not induce suppressor activity in APCs through the PD-1 pathway (57).…”
Section: Advances In the Treatment Of Eaumentioning
confidence: 80%